Whither al-Anbar Province? : five scenarios through 2011 - Bruce, James B. (Occasional paper (Rand Corporation), 2010)
The withdrawal of U.S. forces from Iraq will create a vacuum in the way security is achieved and power is exercised throughout Iraq. As U.S. Marines draw down in al-Anbar Province, significant changes can be expected throughout the province in security, political, economic, and even cultural relationships. In late 2008, RAND convened a series of three one-day workshops bringing together civilian and military analysts and practitioners with experience on al-Anbar Province or comparable expertise on Iraq. Workshops participants identified five relatively distinct futures, or scenarios, for al-Anbar that provide plausible but alternative trajectories for the province between early 2009 and the end of 2011. These scenarios resulted from extensive consideration of the major assumptions that may underlie any future projections and the testing of those assumptions in a variety of exercises. The deliberations also focused on the major factors that will shape the development of one or another scenario.